2018
DOI: 10.3892/or.2018.6902
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β‑catenin inhibition reverses multidrug resistance in pediatric acute lymphoblastic leukemia

Abstract: Although ~80% of newly diagnosed pediatric patients with acute lymphoblastic leukemia (ALL) become disease-free following appropriate treatment, relapses frequently occur, with dismal prognosis. Therefore, it is urgent to develop novel therapeutic modalities. Resistance to chemotherapy is a major obstacle for the treatment of relapsed ALL. It has been indicated that Wnt pathway is potentially associated with leukemia recurrence. In the current study, a vincristine (VCR)-resistant variant of the human ALL cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…As for the Wnt signaling pathway, it was significantly correlated with the pathogenesis of ALL ( Montano et al, 2018 ). Recent findings reported that inhibiting Wnt/β catenin could reverse multidrug resistance in children ALL ( Fu et al, 2019 ). Moreover, the pathway is regulated by many factors.…”
Section: Discussionmentioning
confidence: 99%
“…As for the Wnt signaling pathway, it was significantly correlated with the pathogenesis of ALL ( Montano et al, 2018 ). Recent findings reported that inhibiting Wnt/β catenin could reverse multidrug resistance in children ALL ( Fu et al, 2019 ). Moreover, the pathway is regulated by many factors.…”
Section: Discussionmentioning
confidence: 99%
“…Some chemotherapeutic agents that might be used for ALL treatment (such as doxorubicin, vinblastine or camptothecin) [20] increase the level of oxidative stress, as their antitumor activity depends directly on H 2 O 2 -induced apoptosis [21][22][23][24][25]. One of the critical cytoprotective proteins induced in response to oxidative stress is heme oxygenase-1 (HO-1, encoded by HMOX1 gene localized on chromosome 22q12) [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Mediator of drug resistance -Notch inhibitors sensitize B-ALL cells to chemotherapy (Takam Kamga et al, 2019b). -Wnt inhibition sensitizes B-ALL to chemotherapy (Fu et al, 2019).…”
Section: Notch In Leukemiamentioning
confidence: 99%
“…The functional outcome of this Wnt/Notch crosstalk between MSCs and B-ALL or AML cells is the induction of leukemia cell proliferation, survival and chemoresistance. Consequently, Wnt and/or Notch inhibition through pharmacological modulators, including small molecules inhibitors Niclosamide,GSIs) and Notch blocking antibodies, may sensitize leukemia cells to drug treatment, thus abrogating the protective role of MSC monolayer (Kamdje et al, 2011;Takam Kamga et al, 2016a, 2020Fu et al, 2019). This antileukemic role requires the production of reactive oxygen species (ROS) and the modulation of prosurvival proteins, such as mTor, NF-κB, STAT-3, and Erk (Kamdje et al, 2011;Takam Kamga et al, 2016a,b).…”
Section: Putting Together the Contribution Of Msc-derived Notch And Wmentioning
confidence: 99%